2011
DOI: 10.1080/01488376.2011.547740
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Formal Service Use by Older Chinese: A Case Study on a Naturally Occurring Retirement Community

Abstract: This study examined secondary data from a naturally occurring retirement community in which 296 older Chinese were interviewed to understand and identify the factors related to formal service usage. Regression analysis found that the importance of perception of formal services impacts predicting service use. The results also indicated older female Chinese participants were more likely to use services. Implications for practice and policy to improve access to services by older Chinese were presented and the dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Authors of 20% (13/64) of the articles cited the 1986 definition proposed by Hunt and Gunter-Hunt [3]. Some authors (12/64, 19%) went further to define NORCs by including the percentage or proportion of the community and the age of its residents [17,21,24,29,[31][32][33][36][37][38][39][40]. The range of inclusion criteria cited in the literature is demonstrated in Table 2.…”
Section: Definition Of Norcsmentioning
confidence: 99%
See 4 more Smart Citations
“…Authors of 20% (13/64) of the articles cited the 1986 definition proposed by Hunt and Gunter-Hunt [3]. Some authors (12/64, 19%) went further to define NORCs by including the percentage or proportion of the community and the age of its residents [17,21,24,29,[31][32][33][36][37][38][39][40]. The range of inclusion criteria cited in the literature is demonstrated in Table 2.…”
Section: Definition Of Norcsmentioning
confidence: 99%
“…Studies in which the citations were found Citation Percentage and age [17,21,29] Hunt and Gunter-Hunt [3] 50% are older adults [37] New York State definition [41] 40%-50% of the population is aged >60 years [24,33] Hunt [42] 50% of the residents aged >65 years [31,37,40] Hunt and Ross [43] 50% of the residents should be aged >60 years [38] Lanspery [44] 50% of the residents are aged ≥60 years [39] Hunt [30] ≥50% of the population is aged at least 50 years A subset of articles focused specifically on NORC-SSPs: authors cited definitions from the study by Vladeck [45] that focus on bringing partnerships together to deliver services to concentrated areas of older adults [21,26,31,46]. Although most of the articles written about NORCs were indeed describing a geographical area inhabited by a large proportion of older adults, some authors referred to NORCs as communities with purposeful programs, services, and activities to assist the older adult residents but did not differentiate these as NORC-SSPs or NORC programs.…”
Section: Table 2 Summary Of Naturally Occurring Retirement Community ...mentioning
confidence: 99%
See 3 more Smart Citations